2007
DOI: 10.1128/aac.01479-06
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Piperaquine, Chloroquine, and Amodiaquine on Drug Uptake and of These in Combination with Dihydroartemisinin against Drug-Sensitive and -Resistant Plasmodium falciparum Strains

Abstract: Piperaquine is being developed as a long-acting component in artemisinin combination therapies. It was highly active in vitro and drug interaction studies showed that dihydroartemisinin combinations with piperaquine, chloroquine, and amodiaquine were indifferent tending toward antagonism. Competitive uptake of radiolabeled chloroquine and dihydroartemisinin in combination with other antimalarials was observed.Bis-4-aminoquinoline piperaquine (PPQ) and its analogues have been shown to be potent against chloroqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
1
15
3
Order By: Relevance
“…Interestingly, there was a trend, albeit a slight one, toward a reduced PIP susceptibility in parasites harboring the CVIET PfCRT haplotype. Although no definitive causal relationship was determined, earlier studies have shown a cross-resistance of PIP and CQ (10,34). In our limited panel of parasite lines, genetic modification of the pfmdr1 locus had little effect on parasite susceptibility to PIP (Table 1), despite observations from a number of studies showing a positive correlation between the YYY PfMDR1 haplotype and amodiaquine susceptibility (amodiaquine is structurally related to PIP) (8,11).…”
Section: Discussioncontrasting
confidence: 42%
“…Interestingly, there was a trend, albeit a slight one, toward a reduced PIP susceptibility in parasites harboring the CVIET PfCRT haplotype. Although no definitive causal relationship was determined, earlier studies have shown a cross-resistance of PIP and CQ (10,34). In our limited panel of parasite lines, genetic modification of the pfmdr1 locus had little effect on parasite susceptibility to PIP (Table 1), despite observations from a number of studies showing a positive correlation between the YYY PfMDR1 haplotype and amodiaquine susceptibility (amodiaquine is structurally related to PIP) (8,11).…”
Section: Discussioncontrasting
confidence: 42%
“…In vitro drug susceptibility testing revealed that dihydroartemisinin was 15-times [mean IC 90 of 4.50 Ϯ 0.25 versus 67.51 Ϯ 1.87 nM (n ϭ 3)] and 25.2-times [IC 90 of 4.85 Ϯ 1.51 versus 122.16 Ϯ 23.69 nM (n ϭ 7)] more active than piperaquine in inhibiting the D6 and K1 lines of P. falciparum, respectively. The IC 50 s for dihydroartemisinin (2.57 Ϯ 1.27 nM) and piperaquine (82.06 Ϯ 35.25 nM) were about twofold higher than previously published data using the K1 line (3,4). A likely explanation for this discordance in IC 50 s is the higher human plasma concentration (50% versus 10%) used in the present study compared with others using standard in vitro methods (M. Chavchich, unpublished data).…”
contrasting
confidence: 55%
“…Moreover, the overall good clinical efficacy of DHA-PPQ in treating falciparum malaria in areas of high prevalence of CQ-resistant parasites argues against a shared resistance mechanism between CQ and PPQ (15,47,48). Besides, most in vitro studies of laboratory strains and field parasite isolates failed to detect marked reductions in PPQ sensitivity in comparison with 3D7 or other laboratory strains (25,27,29,30). In most in vitro and ex vivo studies conducted thus far, there was generally a 3-to 4-fold difference in PPQ sensitivity between the most and least susceptible isolates (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, significant correlation of response between PPQ and CQ was also observed in ex vivo studies using parasite isolates from Cameroon (23) and Papua New Guinea (24), albeit PPQ was equally active against CQ-sensitive and -resistant parasites. Studies using laboratory CQ-sensitive and -resistant lines further support the existence of cross-resistance between CQ and PPQ (25,26). In contrast, recent ex vivo and in vitro drug assays using parasites of diverse origins (but mostly from Africa) did not notice significant correlation of responses to CQ and PPQ (27)(28)(29)(30) but detected significant positive correlations in some studies between the responses to PPQ and other antimalarials such as DHA, pyronaridine, amodiaquine, or doxycycline.…”
mentioning
confidence: 86%
See 1 more Smart Citation